Looking ahead to 2024: A focus on transformative leadership and collaboration - McCartney, Matthew P.; Ringler, Claudia (CGIAR, 2024)
This month the news broke that, for the first time, the world has experienced 12 consecutive months with temperatures exceeding 1.5°C above the pre-industrial average. Such heat anomalies wreak havoc on the world’s water resources, energy needs, and ecosystems, with the most disenfranchised communities hit hardest. At the same time, poverty levels in low-income countries remain above pre-COVID-19 levels and food inflation remains unacceptably high, pushing up the number of food- and water-insecure populations, while the biodiversity that our agrifood systems depend on is at greater risk than ever. Given these immense, complex, and interlinked challenges, nexus solutions are urgently required.